A proposed protocol for the registration of evidence-based Educational Psychology programs - de la Fuente, Jesús; Vera-Martínez, Manuel Mariano; Peralta-Sánchez, Francisco Javier; Martínez-Vicente, José Manuel (Frontiers in Psychology, 2022)
The turn to evidence-based interventions is significant for Psychology in general and for Educational Psychology in particular. Although there is a great deal of published evidence for program validation, there is currently no protocol for the evaluation of educational psychology evidence-based intervention programs and there is no General Register of such programs to act as a central information depository. This article has four objectives: (1) To assess the significance of the turn to Evidence-Based Programs in the context of today’s Knowledge Society and Research and Development, Transfer and Innovation (R&Di) activities; (2) To provide a Classification of Programs based on the degree of specialization required for appropriate professional use in line with the requirements of the Code of Ethics in Psychology; (3) To tentatively propose a Protocol for the Registration of Evidence-Based Educational Psychology Programs; (4) Finally, to identify some implications of the protocol. We conclude that there is a need for a General Register of validated programs.